2005
DOI: 10.1111/j.1469-7580.2005.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of melancholia: focus on hypothalamic–pituitary–adrenal axis overactivity and the role of vasopressin

Abstract: Overactivity of the hypothalamic-pituitary-adrenal (HPA) axis characterized by hypercortisolism, adrenal hyperplasia and abnormalities in negative feedback is the most consistently described biological abnormality in melancholic depression. Corticotropin-releasing hormone (CRH) and arginine vasopressin (AVP) are the main secretagogues of the HPA/stress system. Produced in the parvicellular division of the hypothalamic paraventricular nucleus the release of these peptides is influenced by inputs from monoaminer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 46 publications
2
63
0
2
Order By: Relevance
“…70 In similar fashion, patients with major depression show glucocorticoid receptor impairment with decreased glucocorticoid sensitivity, 71 which is compatible with the hypercortisolemia described in depression. 72 It is noteworthy that deficits in the negative feedback of the HPA axis caused by impairment in glucocorticoid receptor function due to depression are resolved after treatment with antidepressants. 73 These findings indicate that disturbances at every level of the HPA axis are relevant for both obesity and depression.…”
Section: A B C D E F G Hmentioning
confidence: 99%
“…70 In similar fashion, patients with major depression show glucocorticoid receptor impairment with decreased glucocorticoid sensitivity, 71 which is compatible with the hypercortisolemia described in depression. 72 It is noteworthy that deficits in the negative feedback of the HPA axis caused by impairment in glucocorticoid receptor function due to depression are resolved after treatment with antidepressants. 73 These findings indicate that disturbances at every level of the HPA axis are relevant for both obesity and depression.…”
Section: A B C D E F G Hmentioning
confidence: 99%
“…Following the combination of AVP and CRH, a much greater synergistic ACTH response is seen. Monoamine neurotransmitters that play a role in depression pathophysiology also have an important effect on HPA activity (8,10). Moreover, selective serotonin re-uptake inhibitors (SSRIs) have an effect on the regulation of the HPA system (decreased DEX-CRH test response).…”
Section: Vasopressin and Depressionmentioning
confidence: 99%
“…Although in acute stress responses CRF is the main activator of ACTH secretion, the AVP/V 3 system seems to play a major role during the adaptation to chronic stress conditions (1,19,26). During chronic stress, it has been shown that the hypothalamic content of AVP and V 3 receptor expression in the brain increases (2) and the peptide becomes the main modulator of the HPA axis (1,13,15,19). SSR149415 is a recently characterized, highly selective, centrally acting nonpeptide antagonist of the V 3 receptor.…”
mentioning
confidence: 99%